Leukopenia in a patient on haloperidol decanoate: a case report - Ahmed, Samreen; Warraich, Saima (International Journal of Basic & Clinical Pharmacology, 2017)
We are reporting a case of leukopenia developed in a patient on haloperidol decanoate injections. A literature review revealed it as an uncommon side effect of antipsychotics; however, regular monitoring of blood cell count is crucial in patients on antipsychotics. In this case report, we discussed the effective doses, side effects, and drug interactions of haloperidol decanoate. Neuroleptic malignant syndrome is a rare but serious side effect of haloperidol.